Orthokeratology lens material copolymer with high mechanical property and preparation method of orthokeratology lens material copolymer
By selecting fluorine-containing monomers and silane monomers in the corneal reshaping mirror material and using two-stage thermal polymerization process, the shortcomings of existing materials in terms of mechanical properties and hydrophilicity are solved, and high oxygen permeability and excellent performance are achieved. The combination of optical performance and good mechanical properties is suitable for a variety of ophthalmic products.
Patent Information
- Application Number
- CN202411815998.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-18
AI Technical Summary
The existing corneal resizing lens materials have shortcomings in terms of mechanical properties and hydrophilicity, and it is difficult to meet the needs of high mechanical properties and wear comfort.
By selecting monomers such as fluorine-containing monomers and methacryloyl (trimethylsiloxy)silane, and using two-stage thermal polymerization process, a corneal resizing lens material with high mechanical properties was prepared. This material improves the oxygen permeability, hydrophilicity and mechanical properties of the material by adjusting the monomer ratio and process conditions.
It realizes the high oxygen permeability, excellent optical performance and good mechanical properties of corneal resizing lens materials, improves wear comfort and biological stability, and is suitable for a variety of ophthalmic products.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a method for preparing a corneal reshaping lens material with high mechanical properties. Background Art
[0002] Orthokeratology (OK) is a product optimized based on the development of hard corneal contact lenses (RGP). It has some characteristics of RGP lenses, but they are not exactly the same. The concept of orthokeratology was first proposed in 1962. In 1989, researchers developed the first reverse geometry hard corneal contact lens - ortho-k lens. In terms of materials, since corneal hypoxia can cause eye diseases such as redness, dry eyes, corneal edema, and corneal ulcers, the oxygen permeability of the material is the core of the safety of OK lenses. On the basis of the oxygen permeability, the biomechanical properties and surface hydrophilic properties of the material also have a great influence on the wearing comfort and shaping effectiveness. Therefore, the material of OK lenses is gradually added from the first generation of polymethyl methacrylate (PMMA) materials to the second generation of silicone or third generation of fluorine-silicone materials with higher oxygen permeability and better wettability on the basis of PMMA materials. This is because the fluffy structure of silicone molecules forms a large number of molecular gaps that allow oxygen to pass through, so silicone materials have good oxygen permeability. The organic fluorine component can promote the dissolution of a large amount of oxygen in the polymer network to improve the oxygen permeability of the material. Patent CN106749877A discloses a high oxygen permeability optical lens material, provides a fluorine-containing raw material for orthokeratology lenses and a preparation method thereof, thereby obtaining a high oxygen permeability orthokeratology lens, but its mechanical properties and hydrophilicity need to be improved. Therefore, to obtain orthokeratology lenses with high mechanical properties, it is necessary to improve its formula and preparation method. Summary of the invention
[0003] The purpose of the present invention is to solve the above-mentioned problems in the prior art and to provide a method for preparing a corneal reshaping lens material with high mechanical properties. By mixing fluorine-containing monomers with other monomers and using a two-stage thermal polymerization process, a corneal reshaping lens with excellent optical and structural properties, strong hydrophilicity and high mechanical properties is prepared.
[0004] In order to achieve the above object, the present invention adopts the following technical scheme:
[0005] A high mechanical performance orthokeratology lens material copolymer, which is copolymerized by the following monomers:
[0006] The first monomer is selected from one or more of hexafluoroisopropyl methacrylate, hexafluoroisopropyl acrylate, heptafluorobutyl methacrylate, octafluoroisobutyl methacrylate, octafluoroisobutyl acrylate, perfluoroalkyl methacrylate, and perfluoroalkyl acrylate;
[0007] The second monomer is selected from methacryl (trimethylsiloxy) silane;
[0008] The hydrophilic monomer is selected from one or more of methacrylic acid, N-vinyl pyrrolidone, N-methyl-N-vinylacetamide, N,N-dimethylacrylamide, and acrylic acid;
[0009] A cross-linking agent is ethylene glycol dimethacrylate;
[0010] The proportion of each monomer in the copolymer is adjusted according to the required properties.
[0011] A method for preparing a corneal reshaping lens material with high mechanical properties, which can improve the mechanical properties of the material and improve the hydrophilicity, comprises the following steps:
[0012] 1) placing the first monomer, the second monomer, the crosslinking agent ethylene glycol dimethacrylate and the initiator azobisisobutyronitrile in a container in a certain mass ratio, and stirring until the solution is clear to prepare a mixed solution;
[0013] 2) Place the mixed solution in a vacuum drying oven for degassing for a certain period of time, add it to the mold, and then transfer it to an oven for two-stage heating polymerization;
[0014] 3) After the reaction is completed, the mold is disassembled to take out the sample, and the remaining raw materials are cleaned with anhydrous ethanol. The sample is then placed in a vacuum drying oven and dried at a certain temperature for a certain period of time to obtain a corneal refractive therapy lens material with high mechanical properties.
[0015] Furthermore, in step 1), the first monomer is selected from one or more of hexafluoroisopropyl methacrylate, hexafluoroisopropyl acrylate, heptafluorobutyl methacrylate, octafluoroisobutyl methacrylate, octafluoroisobutyl acrylate, perfluoroalkyl methacrylate, and perfluoroalkyl acrylate.
[0016] Furthermore, in step 1), the second monomer is selected from methacryl (trimethylsiloxy) silane.
[0017] Furthermore, in step 1), the hydrophilic monomer is selected from one or more of methacrylic acid, N-vinyl pyrrolidone, N-methyl-N-vinylacetamide, N,N-dimethylacrylamide, and acrylic acid.
[0018] Furthermore, in step 1), the ratio of the first monomer to the total mass of the base material is 30.0% to 50.0%, preferably 35.0% to 45.0%.
[0019] Furthermore, in step 1), the ratio of the second monomer to the total mass of the base material is 30.0% to 50.0%, preferably 35.0% to 45.0%.
[0020] Furthermore, in step 1), the ratio of the hydrophilic monomer to the total mass of the base material is 10.0% to 30.0%, preferably 22.0% to 28.0%.
[0021] Furthermore, in step 1), the crosslinking agent accounts for 1.0% to 5.0% of the total mass of the base material, preferably 3.0% to 4.5%. The initiator accounts for 0.1% to 2.0% of the total mass of the base material, preferably 0.5% to 1.5%.
[0022] Furthermore, in step 2), the degassing time is 1 to 10 h, preferably 2 to 4 h; the specific conditions of the two-stage heating polymerization are that the temperature of the first stage is 50 to 100 ° C, preferably 50 to 60 ° C, and the reaction time is 5 to 25 h, preferably 5 to 15 h; the temperature of the second stage is 100 to 150 ° C, preferably 105 to 115 ° C, and the reaction time is 2 to 12 h, preferably 6 to 12 h.
[0023] Furthermore, in step 3), the drying temperature is 50-100°C, preferably 50-60°C, and the drying time is 15-30 h, preferably 20-25 h.
[0024] The prepared material can be used to prepare myopia lenses, orthokeratology lenses or RGP lenses.
[0025] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0026] The raw materials selected by the present invention are cheap and easy to purchase, and the synergistic effect can make the obtained orthokeratology lenses have high oxygen permeability, good hydrophilicity, light transmittance, refractive index and biological stability. The addition of hydrophilic monomers significantly improves the hydrophilicity of the material, helps to reduce the friction and discomfort between the lens and the eye, and improves the wearing comfort. And through a two-stage thermal polymerization process, the reaction rate is controlled to have high mechanical properties. The prepared material may have good biocompatibility and can reduce irritation and inflammatory response to the eyes. The material can be used to prepare a variety of ophthalmic products such as myopia lenses, orthokeratology lenses or RGP lenses, and has broad market application prospects. DETAILED DESCRIPTION
[0027] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with embodiments.
[0028] Example 1
[0029] (1) 0.998 g of hexafluoroisopropyl methacrylate, 1.051 g of methacryloyloxypropyl tris(trimethylsiloxy)silane, 0.42 g of N,N-dimethylacrylamide, 0.42 g of N-methyl-N-vinylacetamide, 0.0825 g of ethylene glycol dimethacrylate, and 0.0125 g of azobisisobutyronitrile were placed in a beaker and stirred until the solution became clear to prepare a mixed solution;
[0030] (2) The mixed solution was placed in a vacuum drying oven for degassing for 6 h, added dropwise to the mold, and then transferred to an 80 °C oven for polymerization reaction for 10 h, and then placed in a 130 °C oven for polymerization reaction for 8 h;
[0031] (3) After the reaction is completed, wait for the sample to cool down, disassemble the mold and take out the sample, clean the remaining raw materials with anhydrous ethanol, and then place the sample in a vacuum drying oven at 80 °C for 20 h to obtain the base material (orthokeratology lens material).
[0032] Example 2
[0033] (1) 1.025 g of heptafluorobutyl methacrylate, 1.145 g of methacryloyloxypropyl tris(trimethylsiloxy)silane, 0.45 g of N-methyl-N-vinyl acetamide, 0.45 g of N-vinyl pyrrolidone, 0.05 g of ethylene glycol dimethacrylate, and 0.0062 g of azobisisobutyronitrile were placed in a beaker and stirred until the solution became clear to prepare a mixed solution;
[0034] (2) The mixed solution was placed in a vacuum drying oven for degassing for 8 h, added dropwise to the mold, and then transferred to a 65°C oven for polymerization reaction for 12 h, and then placed in a 120°C oven for polymerization reaction for 10 h;
[0035] (3) After the reaction is completed, wait for the sample to cool down, disassemble the mold and take out the sample, clean the remaining raw materials with anhydrous ethanol, and then place the sample in a 70 °C vacuum drying oven for 15 h to obtain the base material (orthokeratology lens material).
[0036] Example 3
[0037] (1) 1.225 g of octafluoroisobutyl methacrylate, 1.125 g of methacryloyloxypropyl tris(trimethylsiloxy)silane, 0.39 g of N,N-dimethylacrylamide, 0.39 g of N-vinyl pyrrolidone, 0.078 g of ethylene glycol dimethacrylate, and 0.0079 g of azobisisobutyronitrile were placed in a beaker and stirred until the solution became clear to prepare a mixed solution;
[0038] (2) The mixed solution was placed in a vacuum drying oven for degassing for 4 h, then added dropwise to the mold, and then transferred to a 60 °C oven for polymerization reaction for 20 h, and then placed in a 110 °C oven for polymerization reaction for 12 h;
[0039] (3) After the reaction is completed, wait for the sample to cool down, disassemble the mold and take out the sample, clean the remaining raw materials with anhydrous ethanol, and then place the sample in a 90 °C vacuum drying oven for vacuum drying for 24 h to obtain the base material (orthokeratology lens material).
[0040] Example 4
[0041] (1) 1.48 g of perfluoroalkyl methacrylate, 1.48 g of methacryloyloxypropyl tris(trimethylsiloxy)silane, 0.489 g of N-methyl-N-vinyl acetamide, 0.489 g of N-vinyl pyrrolidone, 0.12 g of ethylene glycol dimethacrylate, and 0.03 g of azobisisobutyronitrile were placed in a beaker and stirred until the solution became clear to prepare a mixed solution;
[0042] (2) The mixed solution was placed in a vacuum drying oven for degassing for 10 hours, added dropwise to the mold, and then transferred to a 70°C oven for polymerization reaction for 15 hours, and then placed in a 125°C oven for polymerization reaction for 6 hours;
[0043] (3) After the reaction is completed, wait for the sample to cool down, disassemble the mold and take out the sample, clean the remaining raw materials with anhydrous ethanol, and then place the sample in a 50 °C vacuum drying oven for 30 h to obtain the base material (orthokeratology lens material).
[0044] Example 5
[0045] (1) 0.757 g of perfluoroalkyl acrylate, 0.686 g of methacryloyloxypropyl tris(trimethylsiloxy)silane, 0.275 g of N,N-dimethylacrylamide, 0.275 g of N-methyl-N-vinylacetamide, 0.068 g of ethylene glycol dimethacrylate, and 0.0089 g of azobisisobutyronitrile were placed in a beaker and stirred until the solution became clear to prepare a mixed solution;
[0046] (2) The mixed solution was placed in a vacuum drying oven for degassing for 5 h, added dropwise to the mold, and then transferred to a 90 °C oven for polymerization reaction for 16 h, and then placed in a 135 °C oven for polymerization reaction for 4 h;
[0047] (3) After the reaction is completed, wait for the sample to cool down, disassemble the mold and take out the sample, clean the remaining raw materials with anhydrous ethanol, and then place the sample in a 60 °C vacuum drying oven for vacuum drying for 22 h to obtain the base material (orthokeratology lens material).
[0048] Example 6
[0049] (1) 0.724 g of 1,1,1,3,3,3-hexafluoroisopropyl methacrylate, 0.889 g of methacryloyloxypropyl tris(trimethylsiloxy)silane, 0.333 g of N,N-dimethylacrylamide, 0.333 g of N-vinyl pyrrolidone, 0.045 g of ethylene glycol dimethacrylate, and 0.0078 g of azobisisobutyronitrile were placed in a beaker and stirred until the solution became clear to prepare a mixed solution;
[0050] (2) The mixed solution was placed in a vacuum drying oven for degassing for 2 h, added dropwise to the mold, and then transferred to a 100 °C oven for polymerization reaction for 22 h, and then placed in a 140 °C oven for polymerization reaction for 10 h;
[0051] (3) After the reaction is completed, wait for the sample to cool down, disassemble the mold and take out the sample, clean the remaining raw materials with anhydrous ethanol, and then place the sample in a 65°C vacuum drying oven for 18 h to obtain the base material (orthokeratology lens material).
[0052] Example 7
[0053] (1) 3.4 g of hexafluoroisopropyl acrylate, 3.4 g of methacryloyloxypropyl tris(trimethylsiloxy)silane, 1.4 g of N,N-dimethylacrylamide, 1.4 g of N-vinyl pyrrolidone, 0.36 g of ethylene glycol dimethacrylate, and 0.095 g of azobisisobutyronitrile were placed in a beaker and stirred until the solution became clear to prepare a mixed solution;
[0054] (2) The mixed solution was placed in a vacuum drying oven for degassing for 6 h, added dropwise to the mold, and then transferred to a 55 °C oven for polymerization reaction for 14 h, and then placed in a 100 °C oven for polymerization reaction for 5 h;
[0055] (3) After the reaction is completed, wait for the sample to cool down, disassemble the mold and take out the sample, clean the remaining raw materials with anhydrous ethanol, and then place the sample in a vacuum drying oven at 85 °C for 20 h to obtain the base material (orthokeratology lens material).
[0056] Example 8
[0057] (1) Place 4.8 g of 1,1,1,3,3,3-hexafluoroisopropyl methacrylate, 4.8 g of methacryloyloxypropyl tris(trimethylsiloxy)silane, 2.1 g of N-methyl-N-vinylacetamide, 2.1 g of N-vinylpyrrolidone, 0.52 g of ethylene glycol dimethacrylate, and 0.1 g of azobisisobutyronitrile in a beaker and stir until the solution becomes clear to prepare a mixed solution;
[0058] (2) The mixed solution was placed in a vacuum drying oven for degassing for 2.5 h, added dropwise to the mold, and then transferred to a 60 °C oven for polymerization reaction for 8 h, and then placed in a 110 °C oven for polymerization reaction for 6 h;
[0059] (3) After the reaction is completed, wait for the sample to cool down, disassemble the mold and take out the sample, clean the remaining raw materials with anhydrous ethanol, and then place the sample in a 60 °C vacuum drying oven for vacuum drying for 30 h to obtain the base material (orthokeratology lens material).
[0060] The performance tests of the high mechanical performance orthokeratology lens materials prepared in Examples 1-8 were performed, and the results are shown in Table 1:
[0061] Oxygen permeability coefficient: tested using the national standard (GB / T 11417.2-2012) coulometric method.
[0062] Refractive Index: Refractive index is measured at 20°C according to ASTM D1218, Standard Test Method for Refractive Index and Refractive Dispersion of Hydrocarbon Liquids.
[0063] Shore hardness: measured using (GB / T11417.6—2012) D-type Shore hardness tester.
[0064] Mechanical properties: measured using an Instron tensile testing machine (GB / T11417.6—2012).
[0065] Water contact angle: measured using a contact angle meter.
[0066] Table 1
[0067]
[0068] As can be seen from Table 1, the high mechanical performance orthokeratology lens materials prepared in Examples 1 to 8 show relatively consistent and stable performance in terms of oxygen permeability, refractive index, Shore hardness, water contact angle and elastic coefficient. These performance parameters are all within a reasonable range, indicating that the materials prepared by the method of the present invention have good wearing comfort and optical properties.
[0069] The raw materials used in the present invention are fluorine silicon materials, hydrophilic monomers, initiators and crosslinking agents. The process adopts a two-stage thermal polymerization method. The process reaction steps are simple, the reaction time is short, and the reaction rate can be controlled, thereby reducing the production cost of orthokeratology lenses. Experiments show that the copolymer has high oxygen permeability and excellent optical properties, and exhibits good mechanical properties compared to similar products. It provides a new and high-performance material option for the field of ophthalmic lenses.
[0070] The above embodiments are only used to help understand the method of the present invention and its core idea. The above description of the disclosed embodiments enables professionals and technicians in this field to implement or use the present invention. Various modifications to these embodiments will be obvious to professionals and technicians in this field, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, for ordinary technicians in this technical field, all equal changes and modifications made according to the scope of the patent application of the present invention shall belong to the scope of the present invention without departing from the principles of the present invention. The present invention will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A high mechanical performance orthokeratology lens material copolymer, characterized in that: The copolymer is formed by copolymerization of the following monomers: The first monomer is selected from one or more of hexafluoroisopropyl methacrylate, hexafluoroisopropyl acrylate, heptafluorobutyl methacrylate, octafluoroisobutyl methacrylate, octafluoroisobutyl acrylate, perfluoroalkyl methacrylate, and perfluoroalkyl acrylate; The second monomer is selected from methacryl (trimethylsiloxy) silane; The hydrophilic monomer is selected from one or more of methacrylic acid, N-vinyl pyrrolidone, N-methyl-N-vinylacetamide, N,N-dimethylacrylamide, and acrylic acid; A cross-linking agent is ethylene glycol dimethacrylate; The proportion of each monomer in the copolymer is adjusted according to the required properties.
2. A method for preparing a high mechanical performance orthokeratology lens material copolymer, characterized in that: The following steps are involved: a) preparing raw materials: mixing the first monomer, the second monomer, the crosslinking agent and the initiator in a certain mass ratio; wherein, The first monomer is selected from one or more of hexafluoroisopropyl methacrylate, hexafluoroisopropyl acrylate, heptafluorobutyl methacrylate, octafluoroisobutyl methacrylate, octafluoroisobutyl acrylate, perfluoroalkyl methacrylate, and perfluoroalkyl acrylate; The second monomer is selected from methacryl (trimethylsiloxy) silane; The hydrophilic monomer is selected from one or more of methacrylic acid, N-vinyl pyrrolidone, N-methyl-N-vinylacetamide, N,N-dimethylacrylamide, and acrylic acid; The cross-linking agent is ethylene glycol dimethacrylate; Azobisisobutyronitrile was used as the initiator; b) Mixing and degassing: Place the above raw materials in a container and stir until the solution becomes clear to obtain a mixed solution, and then place the mixed solution in a vacuum drying oven for degassing; c) Polymerization: Add the degassed mixture into the mold and transfer it to an oven for a two-stage heating polymerization reaction; d) Post-processing: After the reaction is completed, the mold is disassembled to take out the sample, the residual raw materials are cleaned with anhydrous ethanol, and the sample is placed in a vacuum drying oven for drying to obtain a corneal refractive therapy lens material copolymer with high mechanical properties.
3. The method for preparing a high mechanical performance orthokeratology lens material copolymer according to claim 2, characterized in that: The first monomer accounts for 30.0% to 50.0% of the total mass of the base material, the second monomer accounts for 30.0% to 50.0% of the total mass of the base material, the hydrophilic monomer accounts for 10.0% to 30.0% of the total mass of the base material, the cross-linking agent ethylene glycol dimethacrylate accounts for 1.0% to 5.0% of the total mass of the base material, and the initiator azobisisobutyronitrile accounts for 0.1% to 2.0% of the total mass of the base material.
4. The method for preparing a high mechanical performance orthokeratology lens material copolymer according to claim 3, characterized in that: The first monomer accounts for 35.0% to 45.0% of the total mass of the base material, the second monomer accounts for 35.0% to 45.0% of the total mass of the base material, the hydrophilic monomer accounts for 22.0% to 28.0% of the total mass of the base material, the cross-linking agent ethylene glycol dimethacrylate accounts for 3.0% to 4.5% of the total mass of the base material, and the initiator azobisisobutyronitrile accounts for 0.5% to 1.5% of the total mass of the base material.
5. The method for preparing a high mechanical performance orthokeratology lens material copolymer according to claim 2 or 3, characterized in that: The degassing time is 1 to 10 hours, and the specific conditions of the two-stage heating polymerization are that the temperature of the first stage is 50 to 100° C., and the reaction time is 5 to 25 hours; the temperature of the second stage is 100 to 150° C., and the reaction time is 2 to 12 hours.
6. The method for preparing a high mechanical performance orthokeratology lens material copolymer according to claim 5, characterized in that: The degassing time is 2 to 4 hours; the temperature of the first stage is 50 to 60° C., and the reaction time is 5 to 15 hours; the temperature of the second stage is 105 to 115° C., and the reaction time is 6 to 12 hours.
7. The method for preparing a high mechanical performance orthokeratology lens material copolymer according to claim 2, characterized in that: The drying temperature is 50-100° C. and the drying time is 15-30 hours.
8. The method for preparing a high mechanical performance orthokeratology lens material copolymer according to claim 7, characterized in that: The drying temperature is 50-60° C. and the drying time is 20-25 hours.
9. Use of the material prepared according to the preparation method according to any one of claims 2 to 8 in the preparation of myopia lenses, orthokeratology lenses or RGP lenses.
Citation Information
Patent Citations
Silicone hydrogel contact lenses, optical medical devices and compositions thereof
CA2622733A1
Optical lens material with high oxygen permeability and preparation method thereof
CN106749877A
High-oxygen-permeability polyacrylate material as well as preparation method and application thereof
CN113698552A
Mono-end-capped amphipathic organosiloxane macromonomer, silicone hydrogel, corneal contact lens and preparation method therefor
WO2022141794A1